A Critical Analysis of Research with Children: Differences from Research with Adults - Venny Karolina; Sri Buwono; Aminuyati Aminuyati; Hadi Wiyono; Nining Ismiyani (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
Children were considered weak and lack of experience. The perspectives, nevertheless, have changed; children are competent to deliver their voices. Therefore, there is a need to do research with children so that adults can understand their childhood. The principles of research with children and research with adults might differ. The researchers did qualitative study analysing documents, highlighting the differences between them. Three themes appeared. The first is ethical aspect; children's researchers need to gain consent from children's gatekeepers. The second is rapport building; researchers apply unique strategies, such as role-playing to provide comfort during the research. The last is child-rights based approach; researchers should consider that children's insights can contribute to adults' understanding of children's experiences. This study's practical implication is that it contributes information to potential researchers to apply specific strategies for research with children that might not be applied to research with adults because of their maturity nature.